Mitochondrial Metabolism as Target of the Neuroprotective Role of Erythropoietin in Parkinson's Disease - Federica Rey; Sara Ottolenghi; Toniella Giallongo; Alice Balsari; Carla Martinelli; Robert Rey; Raffaele Allevi; Anna Maria Di Giulio; Gian Vincenzo Zuccotti; Serena Mazzucchelli; Roberta Foresti; Michele Samaja; et al. (MDPI AG, 2021)
Existing therapies for Parkinson's disease (PD) are only symptomatic. As erythropoietin (EPO) is emerging for its benefits in neurodegenerative diseases, here, we test the protective effect driven by EPO in in vitro (SH-SY5Y cells challenged by MPP+) and in vivo (C57BL/6J mice administered with MPTP) PD models. EPO restores cell viability in both protective and restorative layouts, enhancing the dopaminergic recovery. Specifically, EPO rescues the PD-induced damage to mitochondria, as shown by transmission electron microscopy, Mitotracker assay and PINK1 expression. Moreover, EPO promotes a rescue of mitochondrial respiration while markedly enhancing the glycolytic rate, as shown by the augmented extracellular acidification rate, contributing to elevated ATP levels in MPP+-challenged cells. In PD mice, EPO intrastriatal infusion markedly improves the outcome of behavioral tests. This is associated with the rescue of dopaminergic markers and decreased neuroinflammation. This study demonstrates cellular and functional recovery following EPO treatment, likely mediated by the 37 Kda isoform of the EPO-receptor. We report for the first time, that EPO-neuroprotection is exerted through restoring ATP levels by accelerating the glycolytic rate. In conclusion, the redox imbalance and neuroinflammation associated with PD may be successfully treated by EPO.